Redistribution in Aegean Palatial Societies Redistribution and the Political Economy: The Evolution of an Idea - Earle, Timothy (American Journal of Archaeology, 2011)
Whether the Bronze Age Aegean economies can be described as "redistributive" depends on how one defines the term. The concept of redistribution itself has undergone several decades of critical archaeological analysis, much of it stemming from my early work in Polynesia. I consider here how Polanyi's ideas about redistributive economies have been expanded since the 1970s. My review complements the article in this Forum by Nakassis et al. and the contribution by Haistead, who discusses why and how the concept of redistribution still matters in studies of the Minoans and Mycenaeans. To some degree, we all agree: chiefs, and later kings, who sought power in archaic societies did so through many highly variable, contingent, and changing means, all designed to support political-economic strategies based on multiple systems of finance. The Bronze Age Aegean societies provide excellent examples of this process, as demonstrated by the contributors to this Forum.
Anthropology; Archaeology
Keywords: Aegean civilization; Bronze age; chiefdoms; economic aspects; kings & rulers; metals; redistribution; wealth

Redistribution in Aegean Palatial Societies Redistribution in Aegean Palatial Societies: Terminology, Scale, and Significance - Halstead, Paul (American Journal of Archaeology, 2011)
Nakassis et al., in their contribution to this Forum, argue that the term "redistribution" has been used with a range of meanings in the context of the Aegean Bronze Age and so obscures rather than illuminates the emergence and functioning of political economies. They call for detailed empirical investigation rather than reliance on ambiguous idealized types. Lupack and Schon concur, arguing respectively that the palace shared control of the Mycenaean economy with sanctuaries and local communities and that centralized production of craft goods (an,d thus elite strategies of wealth finance) developed late at the palace of Pylos. Pullen finds little archaeological support for Renfrew's extrapolation of centralized redistribution to the Early Bronze Age, while Christakis uses evidence of storage to argue the same for Prepalatial Crete and to play down the scale and importance of elite redistribution in the Minoan palaces. The calls for circumspect use of the term "redistribution" and for detailed empirical investigation are applauded, although these five papers arguably do not all attack the same form of redistribution. This response argues that redistribution sensu Polanyi, Finley, and Killen (i.e., centrally administered movements of goods and services without equivalence of value) retains considerable heuristic value in investigation of both textual and archaeological evidence for Bronze Age political economies.
Anthropology; Archaeology
Keywords: Aegean civilization; Eleia (Greece); Greece; Mycenaean civilization; Pylos site (Eleia; Greece); archaelogy; bronze age; economics; redistribution

Hititlerde Devlet Gelirleri, Depolama ve Yeniden Dağıtım - Reyhan, Esma (The Revenues of Hittite State, Storage and Redistribution., 2009)
The economic system of Hittite Kingdom shows parallelism with a description of Polanyi about redistribution system, as "Tributes firstly flow to the capital of an emperor, and then from there to the provinces". This system completely depended upon the social hierarchy. Tributes firstly flow to the capital of an emperor, and then from there to the provinces. This essay examines the tax collection system of the Hittite Empire, especially the aspect of redistribution of the taxes from the capital to the provinces. As the taxes flow firstly into Hattuşa and later to the provinces, we are trying to draw the conceptional frame of the "redistribution in centralized system". This will also make it possible to consider the management structure of the Hittite Empire as well. (English)
History; Archaeology
Keywords: Hattuşa/Boğazköy; Hattuša/Boğazköy; Hitit Devleti; Hitit Ekonomik Sistemi; Hitit Kanunları; Hitit Ritüel Metinleri; Hitit Çiviyazılı Tabletler; Hittite Cuneiform Tablets; Hittite Economic System; Hittite Laws; Hittite Ritual Texts; Hittite State; Hittites; capital cities; dominance (psychology); kings & rulers; storage; tax administration & procedure; tax collection; tax penalties; warehouses